PERANCANGAN STRATEGI PEMASARAN UKM FAUZI MENGGUNAKAN METODE MARKETING MIX DAN SWOT - Betanursanti, Ida; Fajar, Aziz Nur (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2024)
This research aims to formulate a marketing strategy for Fauzi UMKM bolen cakes so that the company can survive and develop using a Marketing Mix and SWOT analysis. Using optimal marketing strategies is the right step to achieve this goal. SWOT analysis is used to analyze a company's strengths, weaknesses, opportunities, and threats so that the company's position can be determined using IFAS and EFAS analysis. The results of this research show that the IFAS matrix has a score of 0.15, and the EFAS has a score of 0.44. At these coordinates, the company's position is in quadrant I. The appropriate marketing strategy is to use an S-O strategy (strengths and opportunities) where the company uses an aggressive strategy in its marketing. Based on the company's position, the appropriate marketing strategy is to increase production and add flavor variants, maintain prices and provide purchase bonuses, open the official stores, and open branches, and utilize existing social media such as WhatsApp, Instagram, and YouTube.